Prevalence of dental caries, oral-health related quality of life, and oral health inequalities among Libyan pre-school children in Benghazi / Lamis Abdelrahim Fathulla Ballo - Lamis Abdelrahim, Fathulla Ballo (2021)
Background: Dental caries persists as a public health problem that significantly affects individuals and societies. Oral health-related quality of life (OHRQoL) is significantly identified as a serious worldwide public health concern. Oral health inequalities exist in most countries, and these disparities in health vary between and within countries. Aim: This study aimed to investigate dental caries prevalence and experience, oral health related quality of life and oral health inequalities and the associated factors among six-year-old children in Benghazi, Libya. Methods: This study was a secondary data analysis of Benghazi Children Dental Health Survey conducted in the year 2017. The survey collected data on oral health status and treatment of children aged 6, 12 and 15 years of age. For this study, we only analysed data for 706 children aged 6 years, which included dentition status based on World Health Organisation diagnostic criteria, and socio-demographic, feeding and oral behavioural information collected via self-administered questionnaires. Information on oral health related quality of life was gathered using Arabic Early Childhood Oral Health Impact Scale (A-ECOHIS). Permission for using data and ethical approval for the study were obtained. Data was analysis using SPSS and level of significant was set at 0.05. Results: A total of 706 children were included in data analysis. 71.1% of participants had at least one decayed tooth (dmft?1). The average scores of dmfs and dmft were 5.39 ± 7.37 and 3.23± 3.32, respectively. Children who were from worse-off families and whose parents reported near bedtime intake of sugars and lower frequency of tooth brushing were more likely to have higher dmfs (P?0.05). OHRQoL impacts (score >0) has been reported by 499 parents (70.7%), with the average score of 5.37± 6.58 for the overall ECOHIS. Child impacts were iv reported by 69.4% of participants, with an average of 4.13 ±4.87. Family impacts were reported by 34% of participant, which has an average of 1.24 ±2.28. The highest mean of scores was 1.29±1.10 in the child symptoms domain and the lowest mean of scores was 0.24±0.36 in the family function domain. Educational level of mothers and fathers, and occupation of fathers significantly impacted the childrens quality of life. Health inequalities were observed in caries experience and OHRQoL of the children. Conclusion: Dental caries prevalence and experience was high in 6 years old Libyan children and was associated with negative impacts on oral health related quality of life. Health inequalities exists in children oral health and oral health related quality of life. The results of this study demonstrating the need to urgent planning of oral health programs in order to tackle these problems. Keywords: Dental Caries ECOHIS OHRQoL Sociodemographic Factors- Behavioural Factors